Реформа государственной службы в Украине на современном этапе: стратегия и приоритеты - Вакарь, Д.А. (Культура народов Причерноморья, 2013)
В статье проанализированы основные причины и принципы реформирования
государственной службы в Украине, раскрываются пути выработки эффективной концепции и
определения основных приоритетов в развитии государственного управления. Современная практика
общественного развития выдвинула на передний план проблемы становления и развития
государственной службы. Таким образом, можно сказать, что государственная служба как
культурный институт - это такой уровень развития системы государственной службы, в котором
компетентность, профессионализм, моральные принципы государственных служащих должны
воплощать этот уровень, создавать условия для ее эффективного влияния на реальную жизнь граждан. У статті проаналізовано основні причини та принципи реформування державної служби в
Україні, розкриваються шляхи вироблення ефективної концепції та визначення основних пріоритетів у
розвитку державного управління. Сучасна практика суспільного розвитку висунула на передній план
проблеми становлення та розвитку державної служби. Таким чином, можна сказати, що державна
служба як культурний інститут - це такий рівень розвитку системи державної служби, в якому
компетентність, професіоналізм, моральні принципи державних службовців мають втілювати цей
рівень, створювати умови для її ефективного впливу на реальне життя громадян.
Ключові слова: державна служба, аппарат управління, реформа. In the article analyzes the main causes and principles of public service reform in Ukraine, the ways
of making effective concepts and definitions of the main priorities in the development of public administration.
The modern practice of social development has highlighted the problems of formation and development of the
public service. Formation of the new Ukrainian state is accompanied by the increasing importance of public
service. The functioning of a modern state apparatus is impossible to imagine without rationally designed, wellestablished
and mandatory formal rules, without strict management mechanism professionalization. Tool and at
the same time the result of a professionalization, in particular, have become civil servants, whose activities are
based on the principles of professional competence, hierarchy and specialization of functions. In this context, of
course, raises the question of the relationship between professionalism and ethics. In view of situation in the
country, the novelty and difficulty of current and strategic objectives, their changes should be regarded as the
primary and priority issues of staffing Civil Service of Ukraine, the management of its staff. Thus, it can be said
that the public service as a cultural institution - is the level of development of the civil service system, in which
the competence, professionalism, moral principles of civil servants must embody this level, to create conditions
for its effective impact on the real lives of citizens.